Systematic-informative algorithmization of flight norms violation hazard estimation and analysis procedure by air traffic controllers - Рева, О. М.; Борсук, С. П. (Science-based technologies, 2017)
Taking into account restrictions set by ICAO for flights in horizontal plane systematic-informative algorithmization of air traffic controllers self-estimation was grounded. That estimation concerns air traffic flight norms violation and takes into account stable and permanent human factor influence upon flight systems safety. Management task solution scheme, decision taking stages and risk grading in air navigation systems are considered. Розглянуто схему вирішення задачі управління, стадії прийняття рішень, ієрархію ризику в аеронавігаційних системах. Known algorithm of American scientist I. Jenis and and L. Mann was improved considering both ICAO qualitative criteria of aviation systems hazard levels and peculiarities of air traffic controllers professional activities. Proposed schrmr of steps and questions will allow air traffic controller to proceed with continuous actions self-analysis during solution taking.